Overcoming Unmet Family Planning Needs in Indonesia: The Crucial Role of Community Empowerment in Addressing Challenges - Susanti, Dewi; Erwani, Erwani; Yusefni, Elda (Alifah Health Science Symposium Proceeding, 2023)
Family planning plays a central role in individual well-being and community development. In Indonesia, with a population of over 270 million people and rapid population growth, family planning has become increasingly important. Unmet Family Planning (FP) Needs in Indonesia remain high, which has serious implications for health and social development. This in-depth study explores the factors contributing to Unmet FP Needs and highlights the crucial role of community empowerment in addressing this issue. The research employs an exploratory qualitative approach, with in-depth interviews and focus group discussions as the primary data collection methods. The findings identify low knowledge of contraception, unsupportive attitudes, the influence of religious factors, and the role of husbands in family planning decisions as key factors. Additionally, limited access to FP services is also a significant barrier. To address these issues, more intensive education, awareness, and socialization efforts are needed, along with strong collaboration with religious leaders and involving husbands in family planning. Improving access to FP services, especially in remote areas, is also critically important. The findings of this study have significant policy implications for reducing Unmet FP Needs in Indonesia.